How cognitive enhancement can change our duties - Santoni de Sio, Filippo; Faulmüller, Nadira; Vincent, Nicole A (Frontiers in Systems Neuroscience, 2014)
This theoretical paper draws the scientific community’s attention to how pharmacological cognitive enhancement may impact on society and law. Namely, if safe, reliable, and effective techniques to enhance mental performance are eventually developed, then this may under some circumstances impose new duties onto people in high-responsibility professions – e.g. surgeons or pilots – to use such substances to minimize risks of adverse outcomes or to increase the likelihood of good outcomes. By discussing this topic, we also hope to encourage scientists to bring their expertise to bear on this current public debate.